PELATIHAN SOSIAL-EMOSI UNTUK MENINGKATKAN EMPATI SISWA DI SEKOLAH INKLUSI JEMBER - Fitri, Arrumaisha (Sociocouns: Journal of Islamic Guidance and Counseling, 2025)
Inclusive education aims to create an equitable learning environment for all students, including those with special needs. However, the dynamics of social relations between regular students and special need students remain a serious challenge, particularly in the form of limited empathy and persistent negative stereotypes toward special need students. This study seeks to examine the effectiveness of Social-Emotional Training in enhancing empathy among regular students in inclusive schools. The research employed a quasi-experimental method with a non-equivalent control group design, involving 25 students from TPA Jember Inclusive Vocational School, divided into experimental and control groups. The training was conducted over two weeks and encompassed five social-emotional components: self-awareness, emotion regulation, behavior monitoring, empathy, and social skills. Empathy was measured before and after the intervention using an empathy scale adapted from Bryant’s Empathy Index. Mixed ANOVA analysis revealed a significant increase in empathy among students in the experimental group compared to the control group (p < 0.01), with an effect size of 48.3%. These findings indicate that social-emotional training can foster empathy among regular students and support the development of an inclusive social environment. This study provides practical contributions to the advancement of psychosocial intervention programs in inclusive schools.